Yu in the Xunzi: toward a precise understanding. Issue 2 (3rd April 2018) - Lewis, Colin J.
ABSTRACT: An ongoing dialogue in Xunzi scholarship addresses the role of yu (欲), often rendered as 'desire, ' in motivation, but little has been said about what yu actually is, or whether the translation of 'desire' accurately reflects Xunzi's use of the term. Employing textual analysis alongside research in cognitive science, most notably work on the so-called 'wanting-liking' distinction, I work toward a more precise understanding of Xunzi's notion of yu and its functions. I suggest that yu be construed as a kind of desire with an emphasis on 'wanting' that, while motivational, differs from broader, less precise notions of desire, and that this feature constitutes a distinctive aspect of Xunzi's philosophy of psychology. In so doing, I propose a particular methodological approach for the interpretation of classical Chinese philosophy: when interpreting concepts that are subjects of empirical inquiry, empirical findings should lead us to favor some interpretations over others.